Waste in Textile and Leather Sectors - Körlü, Ayşegül (IntechOpen, 2020)
In this book in your hands, the relationship between the textile and leather sectors, and the environment is examined from many viewpoints. The book contains many different subjects, from sustainability in the textile and leather sectors to the effect of historical textiles on human health. It will be interesting for readers from many disciplines in science.I thank all the authors contributing to the book and I hope that it will be helpful to the readers.